Subjective Risk Tolerance of South African Investors - Dickason-Koekemoer, Zandri; FerreiraSuné (Journal of Economics and Behavioral Studies, 2018)
In general, the amount of risk an individual is willing to tolerate can be influenced by demographic factors. However, needs for research arise as to whether demographic factors influence the amount of risk investors in South Africa are willing to tolerate. The survey was conducted in 2017 and all South African investors were included in the sample frame. For this study, a sample of 800 was collected and used. Multinomial regression was used to indicate whether there were more than two factors that can influence the four risk tolerance levels of South African investors. The study suggested that gender is a determining factor in the risk tolerance of individuals. African investors were more likely to take the substantial financial risk. Age was also a determining factor of risk tolerance which follows the assumptions of the investor lifecycle where younger investors are more risk tolerant. The study furthermore found that higher annual income attracts more risk-taking while lower-income attracts more risk averseness in individuals. It was lastly observed that married individuals and those that are no longer married will be more likely to be risk-averse. This study makes a significant contribution in profiling investors risk tolerance according to their demographic factors whereby financial institutions can offer more tailored investment options.